2022
DOI: 10.3389/fnmol.2022.852882
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Mechanism of Moxibustion Treatment on Mild Cognitive Impairment Patients: An fMRI Study Using ALFF

Abstract: BackgroundMild Cognitive Impairment (MCI), as a high risk of Alzheimer’s disease (AD), represents a state of cognitive function between normal aging and dementia. Moxibustion may effectively delay the progression of AD, while there is a lack of studies on the treatments in MCI. This study aimed to evaluate the effect of moxibustion treatment revealed by the amplitude of low-frequency fluctuation (ALFF) in MCI.MethodWe enrolled 30 MCI patients and 30 matched healthy controls (HCs) in this study. We used ALFF to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…EA can reduce oxidative stress and anti-apoptotic cell death by increasing superoxide dismutase activity in the brain (Wang et al, 2011 ). MB can inhibit apoptosis and oxidative stress and improve vascular endothelial growth factor inflammation (Lai et al, 2022 ). MB may improve cognitive function in VaD patients by inhibiting hippocampal neuronal apoptosis (Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…EA can reduce oxidative stress and anti-apoptotic cell death by increasing superoxide dismutase activity in the brain (Wang et al, 2011 ). MB can inhibit apoptosis and oxidative stress and improve vascular endothelial growth factor inflammation (Lai et al, 2022 ). MB may improve cognitive function in VaD patients by inhibiting hippocampal neuronal apoptosis (Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral blood flow (rCBF) in the left lateral orbital gyrus was decreased in the dizzy MCI group compared with the non-dizzy MCI group (Na et al, 2020). In an ALFF-based fMRI study, researchers found significantly increased ALFF values in the right lingual gyrus of MCI patients compared with HC (Lai et al, 2022). Occipital gray matter volume correlates with neuropsychological performance in patients with amnestic MCI or mild AD (Arlt et al, 2013).…”
Section: Key Regions Of Interests and Genes Selectionmentioning
confidence: 99%
“…This method used multi-task learning and parameter decomposition to simultaneously identify patternconsistent and pattern-specific brain regions and SNP loci. Furthermore, they proposed a parametric decomposition-based sparse multi-view canonical correlation analysis (PDSMCCA) method to identify modality-sharing and specific information from multimodal data to gain insight into the complex pathology of brain diseases (Zhang et al, 2022). However, the above two algorithms only supported the analysis of multimodal brain imaging and single-modal genetic data.…”
Section: Introductionmentioning
confidence: 99%
“…Moxibustion and acupuncture are important means of treating AD in traditional Chinese medicine ( Cao et al, 2016 ; Rigun et al, 2021 ). Although the beneficial effects of moxibustion and acupuncture for AD have been primarily studied both preclinically and clinically ( Zhou et al, 2014 ; Xie et al, 2021 ; Huang et al, 2022 ; Lai et al, 2022 ; Zhang et al, 2022 ), the real efficacy of these treatments on AD remains inconclusive, and the underlying mechanisms are largely unexplored. It has been shown that moxibustion can increase the flow velocity of cerebrospinal fluid and increase the expression of AQP4 in the cortex of mice ( Chen et al, 2021 ), but it is uncertain whether moxibustion can induce the polarity or dynamical localization of AQP4.…”
Section: Introductionmentioning
confidence: 99%